Electroless nano zinc oxide–activate carbon composite supercapacitor electrode - Faraji, S. (Springer New York LLC, 2016)
An electroless deposition process was used to synthesize the nanostructured zinc oxide (ZnO)–activated carbon (AC) as supercapacitor. The composite oxide was studied by high resolution transmission electron microscopy (HRTEM), scanning electron microscopy (FESEM), energy dispersive X-ray spectroscopy (EDX) and X-ray diffraction analysis (XRD). The electrochemical performance of the nanocomposite was analyzed through cyclic voltammetry (CV) and AC impedance spectroscopy (EIS) in 0.1Â M Na2SO4 as electrolyte. A specific capacitance 187Â FÂ g−1 at a scan rate of 5Â mVÂ s−1 was obtained using cyclic voltammetry (CV) and a nearly rectangular shaped CV curve was observed for the composite oxide. The supercapacitor was quite stable during charge–discharge cycling and exhibited constant capacitance during the long-term cycling. It also yielded a specific capacitance 171Â FÂ g−1 at 5Â mAÂ cm−2 with a high energy density of 21.9Â WhÂ kg−1 and 4.2Â kWÂ kg−1 of power density. Due to unique structure of prepared ZnO–AC nanocomposite, it is a promising candidate for supercapacitor.